an Analysis of the Influence of Brand Image, Sales Promotion, E-WoM, and Positive Emotion on Impulse Buying as a Strategy to Improve Sales Performance of Baso Aci MSMEs on TikTok Shop - Putri, Dinda Triana; Suhud, Usep; Krissanya, Nofriska (LPPPIPublishing, 2025)
This study aims to analyze the influence of brand image, sales promotion, electronic word of mouth (E-WoM), and positive emotion on consumers’ impulse buying behavior in purchasing decisions related to Baso Aci on TikTok Shop. The selected object of this study is Baso Aci Sajodo. Although Baso Aci in general was the most popular product on TikTok Shop in October 2024, the sales performance of Baso Aci Sajodo remained relatively low compared to other products offered by Sajodo. This condition reflects a common issue faced by MSMEs, often caused by uneven and suboptimal marketing strategies. This research uses a quantitative approach through an online questionnaire distributed to 250 respondents who live in Jabodetabek, are at least 17 years old, and who have purchased Baso Aci Sajodo at least twice in the past month on TikTok Shop. Data were analyzed using Structural Equation Modeling (SEM) to examine the relationships between the studied variables and to test the proposed hypotheses. The findings indicate that brand image, sales promotion, electronic word of mouth, and positive emotion have a positive and significant influence on impulse buying. Therefore, this research provides valuable insights for strategic planning, particularly for MSME actors such as Baso Aci Sajodo, in optimizing brand image, offering attractive promotions, generating positive reviews, and building consumers’ positive emotions to enhance the likelihood of impulse buying decisions.